Activitatea economică în mediul rural şi coordonatele ocupării populaţiei - Flavius MIHALACHE (Revista Transilvană de Ştiinţe Administrative, 2013)
This paper is focused on the analyses of two interconnected dimensions of rural Romania: economic life and employment. Using statistical data, it explores the main characteristics of the rural economy in the last two decades. The results identify employment problems and traditional agriculture as the main barriers in the development of the rural areas. For many villages, the non-farming working sector is underdeveloped, while traditional agricultural practices are widespread. Subsistence farming practices exploded after 1990, as a consequence of the transition period, turning the rural Romania into one of the most difficult areas across Europe. The actual coordinates of the rural life need a major policy reform. In this direction, the current system of land ownership represents one of the main areas of intervention (support for land consolidation initiatives and support policy for small farmers being absolutely necessary).